Laparoscopic sacrocolpopexy (LSCP) using an ultra-lightweight polypropylene mesh() - Dwyer, Lucy (Eur J Obstet Gynecol Reprod Biol X, 2019)
OBJECTIVES: Since 2005 the preferred method for surgical treatment of vaginal vault prolapse within the department has been laparoscopic sacrocolpopexy with an ultra-lightweight polypropylene mesh. The study aimed to explore the functional and anatomical outcomes and mesh adverse events of women following this procedure. STUDY DESIGN: All women who had a Laparoscopic Sacrocolpopexy (LSCP) using an ultra-lightweight (19 g/m(2)) polypropylene mesh in two units in the North West of England between March 2005 and January 2013 (n = 238) were invited to participate in the study. Functional outcome data was collected using the Patient Global Impression Questionnaire (PGI-I), the Pelvic Floor Distress Inventory (PFDI-20) and the Electronic Personal Assessment Questionnaire (EPAQ) post-operatively. Anatomical outcome was assessed by Pelvic Organ Prolapse Quantification System (POP-Q) measurement. A mesh palpability assessment was performed and any mesh complications were recorded using the International Continence Society/International Urogynecology Association (ICS/IUGA) classification system. The results were compared to those in our previously published series using the same surgical technique but a standard weight mesh (82.5 g/m(2)). RESULTS: 89% of participants reported that they felt their post-operative condition had improved. POP-Q results revealed that the median position of C changed from −3 pre-op to −7 post-operatively. Mesh was palpable during vaginal examination in only 3 women (3%). No mesh extrusion was identified during the study. CONCLUSIONS: The study demonstrates that LSCP performed with an ultra-lightweight polypropylene mesh improves women’s functional and anatomical symptoms and appears to have a low risk of mesh extrusion.